Changing food webs before and during the Last Glacial Maximum based on stable isotopes of animal bone collagen from Lower Austria - Reiss, Lilian; Mayr, Christoph; Pasda, Kerstin; Einwögerer, Thomas; Händel, Marc; Lücke, Andreas; Maier, Andreas; Wissel, Holger (Journal of Quaternary Science, 2023)
We investigated palaeofood web structures using stable isotope analyses on animal bone collagen from four Upper Palaeolithic sites dated to the Early Gravettian (Krems-Hundssteig and Krems-Wachtberg: 33–31k cal a bp, Langenlois: 31–29k cal a bp) and to the Early Epigravettian (Kammern-Grubgraben: 24–20k cal a bp). In both periods, δ13C values show niche partitioning between hare, horse and mammoth on one side, and reindeer and ibex on the other, indicating different diets and habitats between both herbivore groups. The δ15N differences between carnivores and herbivores suggest a difference of one trophic level during the pre-Last Glacial Maximum (pre-LGM) period at the Early Gravettian sites and a tendency towards secondary carnivores during the LGM at Kammern-Grubgraben. δ15N values of pre-LGM mammoths are elevated in relation to other herbivores but shifted to the level of other herbivores in the LGM. A general δ15N value shift in herbivores of 3.3‰ from the pre-LGM to the LGM is related to climatic deterioration. This may have led to the disappearance of certain ecological niches and to a shift from broader to overlapping ecological herbivore niches shortly before the LGM, as demonstrated by SIBER analyses.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Epigravettian; Gravettian; niche partitioning; δ; δ